2017
DOI: 10.1016/j.semcancer.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Defining the momiome: Promiscuous information transfer by mobile mitochondria and the mitochondrial genome

Abstract: Mitochondria are complex intracellular organelles that have long been identified as the powerhouses of eukaryotic cells because of the central role they play in oxidative metabolism. A resurgence of interest in the study of mitochondria during the past decade has revealed that mitochondria also play key roles in cell signaling, proliferation, cell metabolism and cell death, and that genetic and/or metabolic alterations in mitochondria contribute to a number of diseases, including cancer. Mitochondria have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 329 publications
(402 reference statements)
0
28
0
1
Order By: Relevance
“…In eukaryotic cells, mitochondria take part in intracellular regulations mediated by cross-talk between mitochondria and the nucleus. This interaction is represented by anterograde (nucleus-mitochondrion) and retrograde (mitochondrion-nucleus) signaling [32]. This cross-talk includes exchange by ATP/ADP, regulatory proteins and genetic material going in both directions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In eukaryotic cells, mitochondria take part in intracellular regulations mediated by cross-talk between mitochondria and the nucleus. This interaction is represented by anterograde (nucleus-mitochondrion) and retrograde (mitochondrion-nucleus) signaling [32]. This cross-talk includes exchange by ATP/ADP, regulatory proteins and genetic material going in both directions.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-talk includes exchange by ATP/ADP, regulatory proteins and genetic material going in both directions. Bidirectional transport of genetic material is of primary interest for molecular biologists due to its high relevance to the evolution of eukaryotic genomes [27][28][29] and the occurrence of diseases through regulation of gene expression, possibly by non-coding RNAs originating both from mitochondria [32] and nuclei [31][32][33][34][54][55][56][57]. The so-called "escape" of nucleic acids from nuclei and mitochondria [58] seems to be part of a well-designed strategy of communication of genomes rather than being an occasional stochastic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have multiple important functions, including controlling adenosine triphosphate (ATP) generation, metabolic signalling, proliferation, redox homeostasis, and promotion/suppression of apoptotic signalling pathways. Genetic and/or metabolic alterations in mitochondria contribute to many human diseases, including cancer [1]. Although glycolysis was traditionally considered as the major source of energy in cancer cells, consistent with the so-called "Warburg effect" first suggested almost a century ago, referring to the elevated uptake of glucose that characterizes the majority of cancers, the mitochondrial function known as oxidative phosphorylation (OXPHOS) has been recently recognized to play a key role in oncogenesis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…[1 , 2 Thus, introducing healthy mitochondria into tumor cells is proposed to have a high efficacy in preventing tumor growth. [3,4 Currently,exogenous healthy mitochondria have been utilized in treating several carcinoma, including breast cancer, pancreatic cancer, and glioma, and similar results exhibited the excellent antitumor activity of the healthy mitochondria. [5 , 6 , 7 In our recent studies, we have examined the anti-tumor potential of mitochondria derived from young and aged mouse liver, and found that mitochondria from young mice have stronger anti-melanoma effects in comparison with that of the aged mice.…”
Section: Introductionmentioning
confidence: 99%